A singular therapeutic project and home visits in the training of health professionals: An experience report (International Seven Journal of Health Research, 2023)
This article reports on the experience of home visits by undergraduate medical students at a higher education institution in the interior of the state of São Paulo. With the growing demands for the implementation of comprehensive health care and the humanization of care, promoted not only by current legislation but also by discussions in the health sciences, it has become essential to offer health professionals opportunities to experience realities that contribute to the development of the necessary skills. For this reason, subjects such as Practices of Integration and Health Care - FUNEPE and Community V, offered to third-year medical students at the Penápolis Educational Foundation (FUNEPE), should be the subject of research and study. Therefore, the aim of this study is to shed light on a pedagogical model that gives students the opportunity to experiment with Home Care (HC) and Singular Therapeutic Project (STP) practices.